Evaluation of Blended Learning Effect of Engineering Geology Based on Online Surveys - Binbin Yang; Xiaoming Zhao; Dongqi Tang (Geofluids)
Engineering geology applies geological theories and methods to the practice of engineering activities, evaluates the engineering geological conditions of the engineering site through engineering geological investigation and comprehensive research of theories, solves the engineering geological problems related to engineering activities, predicts and demonstrates the occurrence and development laws of engineering geological problems in the engineering activity area, and puts forward technical measures for prevention and control, so as to contribute to the planning, design, and construction and provide necessary geological and technical data for use and maintenance. Based on the theory of multiattribute decision-making, this paper puts forward the evaluation index system of engineering geology teaching quality in applied universities. A curriculum teaching quality evaluation index system is constructed, which is composed of four main indexes: online resources and teaching, offline teaching process, classroom teaching quality evaluation, and classroom teaching quality evaluation. Furthermore, 11 second-class indices and 28 third-class indices are considered. The judgment matrices and membership degree of each attribute are obtained through use of a questionnaire, and the total weight of each subitem is calculated using the analytic hierarchy process. The calculation results show that the classroom instructional quality of the engineering geology course can be considered excellent; furthermore, other courses could also be evaluated using the same method, where those with low evaluation results can be further improved. Using the fuzzy comprehensive evaluation method based on the analytic hierarchy process, we evaluate the instructional quality, comprehensively consider the nonlinear and fuzzy characteristics of evaluation factors, can scientifically calculate the weight value of each evaluation index, and combine qualitative and quantitative aspects, in order to objectively provide an evaluation of the classroom instructional quality of teachers, which is conducive to the high-quality construction of university courses.